The Socio-Economics of Women Inclusion in Green Construction (Construction Economics and Building, 2017)
The female population represents one of the greatest untapped resources for economic growth and revitalization in most sectors. The purpose of the study was to examine the socio-economics of women’s inclusion in green construction. The study utilized the use of questionnaires which were distributed to female professionals in the Nigerian construction industry. A total of 120 female construction professionals were used for this study. The data gathered was analysed using SPSS v17.0 with tests such as Frequencies, Percentages, Mean Score, ANOVA, and Factor Analysis. The result revealed a low level of participation by women in green construction. Women in construction exhibited moderate participation in Solar panel manufacturing, installation, and maintenance and in the enforcement of environmentally friendly practices on-site. The study revealed that the stressful nature of works, low interest from women, low career growth/progression and low investments in green works are significant barriers affecting women’s inclusion in green construction. In conclusion, the study identified three (3) socio-economic benefits of women’s inclusion in green construction. These are family/women related benefits, environment related benefits, and green energy market related benefits. The study suggested measures to increase women’s participation in green construction.